Evaluación del comportamiento agronómico de cuatro líneas promisorias y una variedad de trigo durum bajo las condiciones agroclimáticas de la Estación Experimental Santa Catalina – INIAP - Herrera Farinango, Yesenia Elizabeth (2024)
In Ecuador, there is a low demand for wheat in the last 15 years, so 95-96% is imported grain, the problem of low production of this cereal is due to the fact that most wheat producers were dedicated to other crops because they were more economically viable. The present research was carried out at the Santa Catalina Experimental Station - INIAP and the main objective was to evaluate the agronomic performance of four promising lines and one variety of durum wheat (Triticum durum), taking into account the agroclimatic conditions of the site under study. The purpose was to find lines with better adaptability, resistance and yield for the production of this cereal in this area. A completely randomized design was used with three replications and five treatments in plots of 3.6 m2 with a total of 15 experimental units. Variables such as emergence, number of tillers, days to heading, plant height, number of speakes m2 , number of grains spike, number of grains spike, type of straw, disease reaction, grain yield, hectoliter weight, type of grain and protein were evaluated. For the evaluation we used the manual º111 called "Parameter evaluation and selection of cereals" which helped us to determine each of the evaluation variables. For the data analysis, a normality test and Tukey at 5% were used for the analysis of variance, and for the scale variables, average tables were used. The data obtained determined that the parameter with the best yield was UEB-carnavalero with 2466.66 k/g ha-1 followed by the promising line A-01 with a yield of 1975 k/g ha-1 , in contrast to the promising line A-02 with a yield of 1557.41 k/g ha-1 and the other line A-03 with a yield of 1551.56 k/g ha-1. With the data obtained, the line with the best yield for the study site is the variety UEB-Carnavalero, since it maintains its standard and has not been degraded, so it is advisable to continue with the investigation of this variety and the other lines.